Toponymy, history and dunes: the lost place of La Barrosa of Doñana - Muñoz-Reinoso, José Carlos (Revista de Estudios Andaluces, 2023)
The present work has four objectives: 1) to document the existence of a place called La Barrosa (barro= mud) on the ancient coast of Doñana, 2) to locate it spatially, 3) to hypothesise about its origin, and 4) to describe its uses over time. To this end, written and cartographic sources from the 15th to 18th centuries have been analysed and contrasted with the geomorphological and archaeological information available for the area. The analysis of documentary sources has made it possible not only to determine the spatial location of La Barrosa, but also to appreciate its temporal evolution in relation to the dune dynamics and its changes of use. La Barrosa must have disappeared during the first half of the 17th century with the set in motion of the dunes and coastal progradation. However, the presence of mud appears in the description of the Doñana coast in 1743 with a new place name, El Guerrero. The description of the existence of different materials suggests that a Roman settlement may have existed at the site of La Barrosa/El Guerrero.